THE ROLE OF ARTIFICIAL INTELLIGENCE IN EDUCATION - Abdulaziz Ashurov,; Gʻulomova Shakhzoda,; Muzafarova Sevinch,; Toshmirzayeva Sitora, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article explores how artificial intelligence (AI) is reshaping education. AI is not only personalizing learning for students but also easing teachers’ workloads and introducing innovative tools for both students and educators. Adaptive platforms like DreamBox and Knewton adjust lessons according to each student’s needs, making learning more engaging. AI also automates tasks such as grading and scheduling, allowing teachers to spend more time with students. Additionally, AI-powered chatbots and virtual assistants can answer questions and provide tutoring in various subjects. AI enhances accessibility as well, with speech recognition and translation tools helping students with hearing difficulties or those from different language backgrounds, making education more inclusive and equitable.